Predictive Validity of the Bayley-III Cognitive Scores at 6 Months for Cognitive Outcomes at 24 Months in Very-Low-Birth-Weight Infants - Liu, Tzu-Yu; Chang, Jui-Hsing; Peng, Chun-Chih; Hsu, Chyong-Hsin; Jim, Wai-Tim; Lin, Jia-Ying; Chen, Chia-Huei; Li, Sung-Tse; Chang, Hung-Yang (Frontiers in Pediatrics, 2021)
Purpose: To assess the predictive validity of the Bayley Scales of Infant and Toddler Development, Third Edition (Bayley-III) cognitive scores at 6 months of corrected age (CA) for cognitive outcomes at 24 months of CA in very-low-birth-weight (VLBW) infants and investigate the predictors of change in cognitive outcomes. Methods: We retrospectively evaluated VLBW children enrolled in the Taiwan Premature Infant Follow-up Network between 2010 and 2015 and completed the Bayley-III at CA of 6 and 24 months. The predictive validity of the cognitive performance at 6-month CA for the cognitive outcomes at 24-month CA was analyzed. The positive and negative predictive factors were also evaluated using logistic regression. Cut-off scores of <70 and <85 were used to identify lower functioning groups based on the Bayley-III definition. Results: A total of 2972 VLBW children, born with a mean weight of 1116.4 ± 257.5 g and mean gestational age of 29.0 ± 2.8 weeks, were evaluated. A cognitive score of <70 at 6-month CA had a positive predictive value (PPV) of 27.4% (95% confidence interval [CI]: 19.2-35.7%) for a cognitive score of <70 at 24-month CA, while the negative predictive value (NPV) was 97.3% (95% CI: 96.7–97.9%). A cut-off score of 85 had a PPV of 33.6% (95% CI: 28.1–39.0%) and an NPV of 87.7% (95% CI: 86.4–88.9%). Abnormal muscle tone at 6 months was a risk factor for cognitive function decline at 24 months for both Bayley-III cognitive cut-off scores: scores of 70 (adjusted odds ratio [AOR]: 2.8; 95% CI: 1.5–5.5) and 85 (AOR: 2.6; 95% CI: 1.6–4.1). Lower maternal socioeconomic status was associated with a worsening of the cognitive function in infants at 24 months who scored ≥85 at 6 months (AOR: 1.6; 95% CI: 1.2–2.0). Conclusion: Subnormal Bayley-III cognitive scores at 6-month CA were not predictive of subnormal cognitive function at 24-month CA. In children with normal cognition during early infancy, abnormal muscle tone and lower maternal socioeconomic status may influence the cognitive developing process; this highlighted the importance of early identification of high risk infants and complete preterm infant-associated public health policies to promote an improved neurodevelopmental outcome.